Fe-aminoclay-entrapping electrospun polyacrylonitrile nanofibers (FeAC-PAN NFs) for environmental engineering applications - Lee, Jae-Young; Choi, Saehae; Song, Dongsu; Park, Seung Bin; Kim, Moon Il; Lee, Go-Woon; Lee, Hyun Uk; Lee, Young-Chul (The Korean journal of chemical engineering, 2015)
Electrospun polyacrylonitrile nanofibers (PAN NFs) with entrapped water-soluble Fe-aminoclay (FeAC) [FeAC-PAN NFs] were prepared. Slow dropwise addition of water-soluble FeAC into a PAN solution, less aggregated of FeAC into electrospun PAN NFs was one-pot evolved without FeAC post-decoration onto as-prepared PAN NFs. Taking into consideration both the Fe 3+ source in FeAC and the improved surface hydrophilicity, the feasibility of Fentonlike reaction for decolorization of cationic model dye methylene blue (MB) under 6 hrs UV-light irradiation was established. In the case where FeAC-PAN NFs were enhanced by hydrogen peroxide (H 2 O 2 ) injection, the apparent kinetic reaction rates were increased relative to those for the PAN NFs. Thus, our flexible FeAC-PAN NF mats can be effectively utilized in water/waste treatment and other environmental engineering applications.